Fundamental Breach Of Contract: A Comparative Review Of The Cisg and Upicc in International Commercial Contract - Widyadhana, Putri Batari; Lauw, Desi Yanti Yohanes (Action Research Literate, 2025)
The concept of fundamental breach forms a cornerstone of international commercial contract law, as it determines the circumstances in which a party may terminate the contract and seek appropriate remedies. In the context of cross-border transactions, where parties often come from different legal traditions, a clear understanding of this doctrine is essential to ensure legal certainty and protect legitimate commercial expectations. The notion of fundamental breach is addressed under both the United Nations Convention on Contracts for the International Sale of Goods (CISG) and the UNIDROIT Principles of International Commercial Contracts (UPICC), though these instruments adopt distinct approaches. The CISG sets a structured framework, requiring that the breach substantially deprive the injured party of its contractual expectations and that this result be foreseeable to the breaching party. In contrast, the UPICC focuses on substantial non-performance and considers additional elements, including whether strict compliance was of the essence, whether the non-performance was intentional or reckless, and whether future performance can reasonably be relied upon. These differing approaches raise important questions regarding their practical implications for parties to international commercial contracts. The authors conclude that while both frameworks aim to balance legal certainty with fairness, the CISG provides a more defined standard, whereas the UPICC offers greater flexibility by focusing on the impairment of the aggrieved party’s contractual interests.